Initiation of adjuvant chemotherapy within 8 weeks of elective colorectal resection improves overall survival regardless of reoperation. (3rd November 2016) - Nachiappan, S.; Askari, A.; Mamidanna, R.; Munasinghe, A.; Currie, A.; Stebbing, J.; Faiz, O.
Abstract: Aim: Reoperation after elective colorectal resection may delay the start of adjuvant chemotherapy (AC). The study investigated the dual impact of a reoperation and AC delay on overall survival (OS). Method: The Hospital Episode Statistics database was analysed between 1997 and 2012. Patients were divided into colon and rectal cancer cohorts and data were analysed based on whether there was delay in receiving AC beyond 8 weeks and whether a patient suffered reoperation within 30 days. Multivariate regression analysis was undertaken to investigate the relationship between delay in giving AC and reoperation and their combined effect on OS. Results: Logistic regression showed reoperation, amongst other things, to be an independent predictor of AC delay, in both colon and rectal cancer (colon, odds ratio 2.31, P  < 0.001; rectal, odds ratio 2.19, P  < 0.001). There was no significant difference in OS between patients who had no AC delay but suffered a reoperation and patients who had no AC delay and no reoperation. Patients who had AC delay but no reoperation, however, had significantly worse OS compared to those who had no AC delay and no reoperation [colon, hazard ratio (HR) 1.16, P  < 0.001; rectal, HR 1.17, P  < 0.001]. Individuals who had both AC delay and a reoperation also had worse OS compared with patients who had neither (colon, HR 1.33, P  = 0.037; rectal, HR 1.38, P  < 0.001). Conclusion: Delayed receipt of AC beyond 8 weeks after surgery is associated with significantly reduced OS regardless of reoperation status in both colon and rectal cancer patients.